A formulation for the unsteady aerodynamics of floating wind turbines, with focus on the global system dynamics - Bayati, Ilmas; Belloli, Marco; Bernini, Luca; Zasso, Alberto (Volume 10: Ocean Renewable Energy, 2017)
This paper proposes a formulation for the assessment of the unsteady aerodynamics of floating offshore wind turbines, based on wind tunnel experiments through surge and pitch imposed motions on the 1/75 DTU 10 MW scale model. Rotor thrust and torque were analysed out of a set of different combinations of amplitudes and frequencies of the imposed mono-harmonic motion, following the idea of splitting these forces into steady and unsteady contributions, respectively through steady and unsteady aerodynamic coefficients. The latter were analysed, for different tip-speed ratios, both experimentally and numerically, with respect to a newly introduced parameter, the "wake reduced velocity", which turned out to be effective in the description of the unsteady regime. Experimental results have shown good consistency of the formulation and put the basis for further studies on this topic, for the comprehension of this phenomenon and for the development of reduced-order models for control purposes, with the focus of the global system dynamics.